Perspectives in the use of tannins as alternative to antimicrobial growth promoter factors in poultry - Redondo, Leandro M.; Chacana, Pablo A.; Dominguez, Johana E.; Fernandez Miyakawa, Mariano E. (Frontiers in Microbiology, 2014)
Antibiotics have been included in the formulation of feed for livestock production for more than 40 years as a strategy to improve feed conversion rates and to reduce costs. The use of antimicrobials as growth-promoting factors (AGP) in sub-therapeutic doses for long periods is particularly favorable to select antimicrobial-resistant microorganisms. In the last years, global concern about development of antimicrobial resistance and transference of resistance genes from animal to human strains has been arising. Removal of AGP from animal diets involves a tremendous pressure on the livestock and poultry farmers, one of the main consequences being a substantial increase in the incidence of infectious diseases with the related increase in the use of antibiotics for therapy and, concomitantly, economic cost. Therefore, alternatives to AGP are urgently needed. The challenge is to implement new alternatives without affecting the production performances of livestock and also avoiding the increase of antimicrobial resistant microorganisms. Plant extracts and purified derived substances are showing promising results for food animal production, either from their efficacy as well as from an economical point of view. Tannins are plant derived compounds that are being successfully used as additives in feed poultry to control diseases and to improve animal performance. Successful use of any of these extracts as feed additive must ensure a product of consistent quality in enough quantities to fulfill the actual requirements of the poultry industry. Chestnut (hydrolizable) and Quebracho (condennsed) tannins are probably the most readily available commercial products that are covering those needs. The present report intends to analyze the available data supporting their use.